Integrated transcriptomics, metabolomics and physiological analyses reveal differential response mechanisms of wheat to cadmium and/or salinity stress - Yue, Zonghao; Liu, Yongchuang; Zheng, Limin; Zhang, Qiaoyang; Wang, Yifan; Hao, Yuwen; Zhang, Mengke; Chen, Yanjuan; Wang, Zhengbing; He, Le; Ma, Keshi (Frontiers in Plant Science, 2024)
Many soils face dual challenges of cadmium (Cd) contamination and salinization. However, the response of crops, especially wheat, to combined Cd and salinity stress is not understood. Here, wheat was grown in a hydroponic model for 14 days under single and combined Cd and NaCl stresses. Growth parameters, tissue Cd2+ and Na+ contents, and leaf chlorophyll (Chl), O2•−, and MDA levels were determined. Comparative transcriptomic and metabolomic analyses of the leaves were performed. The results showed that combined stress had a greater inhibitory effect on Chl contents and generated more O2•− and MDA, resulting in more severe wheat growth retardation than those under Cd or NaCl stress. Stress-induced decrease in Chl levels may be attributed to the inhibition of Chl biosynthesis, activation of Chl degradation, or a decline in glutamate content. Cd addition weakened the promotional effect of NaCl on SOS1 gene expression, thereby increasing the Na+ content. Contrastingly, NaCl supplementation downregulated the Nramp and ZIP gene expressions related to Cd uptake and transport, thereby impeding Cd2+ accumulation. All stresses enhanced tryptophan content via promoting tryptophan biosynthesis. Meanwhile, Cd and NaCl stresses activated phenylpropanoid biosynthesis and purine metabolism, respectively, thereby increasing the levels of caffeic acid, fumaric acid, and uric acid. Activating the TCA cycle was important in the wheat’s response to combined stress. Additionally, NaCl and combined stresses affected starch and sucrose metabolism, resulting in sucrose and trehalose accumulation. Our findings provide a comprehensive understanding of the response of wheat to the combined Cd and salinity stress.